Heuristic model of education and a prototype of a system for remote siren activation in emergency - Bereš, Paun Josif; Bereš, Kristian Paun (Vojnotehnički glasnik / Military Technical Courier, 2013)
A heuristic models of methodical innovation with special emphasis on training of team members to work in emergency situations, where each team member must be aware of the importance of their work, must know and apply a methodology for finding the best solutions and feel satisfaction with the results as an individual and as a part of that team, are proposed in this paper. Heuristic approach to the problems of teaching in emergency situations should allow team members to come up with the creative process of acquiring knowledge, to learn to think and develop skills for education. It is, therefore, such an approach that is not based on passive observation of phenomena and impersonation performed by a teacher, but establishes an active relationship to phenomena of thought and introduces the team members in their own research of the heuristic concept problems with the range of solutions - in this case, " Digital Communications - a program of operational functions of mobile phones "), the function of emergency situations, the example of a prototype system for automatic activation of the alert - sirens.